Barriers and enablers to the implementation of one health strategies in developing countries: a systematic review - Daniele Sandra Yopa; Douglas Mbang Massom; Gbètogo Maxime Kiki; Gbètogo Maxime Kiki; Ramde Wendkoaghenda Sophie; Sylvie Fasine; Oumou Thiam; Lassane Zinaba; Patrice Ngangue; Patrice Ngangue; Patrice Ngangue; Patrice Ngangue (Frontiers Media S.A., 2023)
IntroductionOne Health is a concept that establishes the link between humans, animals and the environment in a collaborative approach. Since One Health's inception, several interventions have been developed in many regions and countries worldwide to tackle complex health problems, including epidemics and pandemics. In the developed world, many collaborative platforms have been created with an international strategy to address issues specific or not to their environment. Unfortunately, there is a lack of synthesis on the challenges and opportunities Low and Middle-Income Countries (LMICs) face.MethodsFollowing The Preferred Reporting Elements for PRISMA Systematic Reviews and Meta-Analyses (PRISMA), we conducted a systematic review. We applied a search strategy to electronic bibliographic databases (PubMed, Embase, Global Health, Web of Science and CINAHL). We assessed the included articles' quality using the Mixed Methods Appraisal tool (MMAT).Results and discussionA total of 424 articles were initially identified through the electronic database search. After removing duplicates (n = 68), 356 articles were screened for title and abstract, and 16 were retained for full-text screening. The identified barriers were the lack of political will, weak governance and lack of human, financial and logistics resources. Concerning the enablers, we listed the existence of a reference framework document for One Health activities, good coordination between the different sectors at the various levels, the importance of joint and multisectoral meetings that advocated the One Health approach and the Availability of funds and adequate resources coupled with the support of Technical and Financial partners.ConclusionOne Health strategy and interventions must be implemented widely to address the rising burden of emerging infectious diseases, zoonotic diseases, and antimicrobial resistance. Addressing those challenges and reinforcing the enablers to promote managing global health challenges is necessary.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/record_email.php, Unique Identifier: CRD42023393693.